Attack on Titan. 30 - Isayama, Hajime, 1986- (Kodansha Comics, 2020)
"To activate the true power of the Founding Titan that courses through his veins, Eren must make contact with Zeke, a Titan of royal blood. Though Zeke has escaped Levi and the Survey Corps, he's made little headway before the Marleyan military and its Titan warriors attack. Eren pummels his way through the Marleyan trap and past his former friends, but as the battle rages, he stumbles into a situation far beyond what his brother could have planned."--Provided by publisher.